Gender differences in peak muscle performance during growth - Dore, E.; Martin, R.; Ratel, S.; Duche, P.; Bedu, M.; van Praagh, E. (International Journal of Sports Medicine, 2005)
Gender-related differences in maximal leg muscle power were examined in 496 females and 426 males aged 8 to 20 years. Cycling peak power (CPP, including the force required to accelerate the flywheel of the cycle ergometer) was measured during three sprints. Optimal velocity (Vopt, velocity at CPP) was also determined. No gender-differences were observed in anthropometric characteristics and cycling performance between 8- and 14-year-old. From age 14, however, males showed a higher CPP than females, but also a higher lean leg volume (LLV, assessed by anthropometry). Allometric relationship between CPP and LLV (CPP = a · LLV b) showed a clear gender-differentiation between 14- and 16-year-old: LLV exponent (b) was 1.05 in males vs. 0.74 in females. From 16 years onwards, analysis of covariance (ANCOVA) showed that the slopes of the CPP-LLV relationship were similar in both genders, but the intercepts differed. In other words, for a similar LLV, males showed greater CPP than females. It was suggested that this sex-related difference was due to total body fat increase, and more specifically lower-limb fat increase during puberty in girls, whilst the boys experienced increased lean body mass. Considering that the same gender-related difference was observed for optimal velocity adjusted for leg length, other factors such as fibre type variability or (and) neuromuscular activation might also be partly responsible for the higher peak muscle performance observed in males.